Find your Math Personality!

Find your Math Personality!

# If (6y - 11)(6y + 11) = ay^{2} - b, what is the value of a?

**Solution:**

Given: (6y − 11)(6y + 11) = ay^{2} − b -------------- (1)

To find: The value of 'a'

We will use the multiplication of algebraic expressions to solve the LHS of (6y − 11)(6y + 11) = ay^{2} − b

Let's solve the LHS = (6y − 11)(6y + 11)

Using the algebraic identity (a + b) (a - b) = a^{2} - b^{2} we get,

(6y − 11)(6y + 11) = 36y^{2} - 121

Now, comparing 36y^{2} - 121 with the RHS of equation (1) : ay^{2} − b

⇒ ay^{2} − b = 36y^{2} - 121

Thus, a = 36, b = 121

We can use Cuemath's online polynomial calculator to perform arithmetic operations on polynomials.

Thus, the value of 'a' for the given equation (6y − 11)(6y + 11) = ay^{2} − b is 36.

## If (6y - 11)(6y + 11) = ay^{2} - b, what is the value of a?

**Summary:**

If (6y - 11)(6y + 11) = ay^{2} - b, the value of a is 36.

Math worksheets and

visual curriculum

visual curriculum